Relationship Marketing on Loyal Customer: A Descriptive Study of Total Bangun Persada's Customer Care Department - Rizki Jaya Putra; Elke Alexandrina (Universitas Multimedia Nusantara, 2019)
Total Bangun Persada (TOTAL) is a construction company that builds international-standard buildings and focuses on high-end market segmentation. It has Customer Care Department which maintains relationships by answering customers' inquiries. TOTAL's Customer Care - after sales service takes place after the project maintenance period, to support TOTAL's core service: